Defining a pattern in the loss of integrity by ribbed plates under fire conditions - Sidnei, Stanislav; Gonchar, Serhii; Zhuravskij, Maxim; Matsyk, Ihor; Nozhko, Ihor; Petukhova, Olena; Shnal, Taras; Vykhrystenko, Viktor (Eastern-European Journal of Enterprise Technologies, 2024)
This paper reports a study aimed at assessing fire resistance of reinforced concrete ribbed slabs at the onset of integrity loss limit state. EN 1992-1-2 lacks calculation methodology for determining the limit of fire resistance of reinforced concrete slabs when the limit state of integrity loss occurs. Scientific works are focused on two limit states of fire resistance: load-bearing capacity and heat-insulating capacity. Experimental tests are criticized because of difficulties in registering signs of the onset of the limit state of loss of integrity, in particular due to the need to control the unheated surface of the ribbed plate during a fire under the action of mechanical load. Therefore, there is no calculation methodology for assessing the fire resistance of reinforced concrete ribbed slabs upon the onset of the limit state of loss of integrity. At the same time, to ensure the safe evacuation of people in the event of a fire, to prevent the spread of fire, as well as to carry out the effective work of rescuers, it is necessary to use building structures with guaranteed fire resistance classes. The paper reports the results of solving thermal engineering and static problems, which relate to the temperature distribution and stress-strain state of the investigated ribbed plate. Conducting research into the fire resistance of reinforced concrete ribbed slabs, taking into account the onset of the limit state of loss of integrity, made it possible to establish the dependence of the fire resistance limit of these structures on the loss of integrity on the level of applied mechanical load. The resulting dependence plot makes it possible to evaluate reinforced concrete ribbed slabs according to the criterion of the onset of the limit state of loss of integrity, which provides an opportunity to determine fire resistance more objectively